A study on defect of jointing component for IBS (precast concrete) / Muhamad Amin A. Bakar. - A. Bakar, Muhamad Amin (2010)
Industrialized building system (IBS) for residential use is still low in Malaysia. Mostly the government quarters is using the IBS system. The study is focus on precast concrete housing only. The most important in precast concrete (IBS) system is he jointing of component. Failure on jointing will affect overall of the building. Nowadays, there are many complaints from occupant about the defect on their house that use IBS system(precast concrete). Damage caused by the weakness of maintenance, design consideration and poor construction work. So that the building need to be maintained for comfortable and safety of occupant. Furthermore this dissertation was study to assess types of defect jointing component and identify the causes of the defect at apartment Putrajaya. The data were collected by checklist survey. In short, this dissertation will study on defect jointing component precast concrete housing focus on defect and caused of defect. It is hope that can come out with rational, recommendation regarding the study area.